Cerebellar lobule atrophy and disability in progressive MS. Issue 12 (26th August 2017) - Cocozza, Sirio; Petracca, Maria; Mormina, Enricomaria; Buyukturkoglu, Korhan; Podranski, Kornelius; Heinig, Monika M; Pontillo, Giuseppe; Russo, Camilla; Tedeschi, Enrico; Russo, Cinzia Valeria; Costabile, Teresa; Lanzillo, Roberta; et al.
Abstract : Objective: To investigate global and lobular cerebellar volumetries in patients with progressive multiple sclerosis (MS), testing the contribution of cerebellar lobular atrophy to both motor and cognitive performances. Methods: Eighty-two patients with progressive MS and 46 healthy controls (HC) were enrolled in this cross-sectional study. Clinical evaluation included motor and cognitive testing: Expanded Disability Status Scale, cerebellar Functional System score, Timed 25-Foot Walk Test, 9-Hole Peg Test (9-HPT), Symbol Digit Modalities Test (SDMT), Brief Visuospatial Memory Test–Revised (BVMT) and California Verbal Learning Test II (CVLT). Cerebellar volumes were automatically obtained using the Spatially Unbiased Infratentorial Toolbox. A hierarchical multiple linear regression analysis was performed to assess the relationship between MRI variables of supratentorial and cerebellar damage (grey matter fraction, T2 lesion volume, metrics of cerebellar atrophy and cerebellar lesion volume) and motor/cognitive scores. Results: Patients with MS exhibited lower cerebellar volumes compared with HC. Regression analysis showed that cerebellar metrics accounted for extra variance in both motor and cognitive performances, with cerebellar lesion volume, cerebellar Lobules VI, Crus I and VIIIa atrophy being independent predictors of 9-HPT, SDMT, BVMT and CVLT performances. Conclusions: Atrophy of specific cerebellar lobules explains different aspects of motor and cognitive disability in patients with progressive MS. Investigation of cerebellar involvement provides further insight into the pathophysiological basis of clinical disability in progressive MS.